Strategi Badan Usaha Milik Kampung Rindang Jaya Tembudan Dalam Pengembangan Destinasi Wisata Tulung Ni Lenggo Di Kecamatan Batu Putih Kabupaten Berau - Yogi Prasetyo Putra (Jurnal Administrasi Bisnis Fisipol Unmul, 2022)
This study aims to find out about the strategies and obstacles of the Rindang Jaya Tembudan Village Owned Enterprise in developing the Tulung Ni Lenggo tourist destination in Batu Putih District, Berau Regency. In analyzing the strategies and barriers of this research, the authors focus on five aspects in the development of tourist destinations, namely attractions, accessibility, amenities, public and institutional facilities and the application of the concept of sustainable tourism development. This research is a descriptive research with qualitative research methods that use data collection in the form of observation, interviews and documentation. Based on theoretical studies and field analysis, the strategy implemented by the Rindang Jaya Tembudan Village Owned Enterprise in the development of the Tulung Ni Lenggo tourist destination has been going well. This is indicated by the implementation of a strategy that has been based on five aspects of tourism destination development and the application of the concept of sustainable tourism. The obstacles faced are the awareness and concern of the people of Tembudan Village towards the development of the Tulung Ni Lenggo tourist destination which is still low and the budget for the construction of the Tulung Ni Lenggo facility from the government is uncertain.